From Silicon Valley to Shenzhen: Global Production and Work in the IT Industry - Lüthje, Boy; Hürtgen, Stefanie; Pawlicki, Peter; Sproll, Martina (Rowman & Littlefield Publishers, 2013)
This seminal study explores the significant changes in the global IT industry as production has shifted from the developed world to massive sites in the developing world that house hundreds of thousands of workers in appalling low-wage conditions to minimize labor costs. Yet little is known about this phenomenon as the major contract manufacturers deliberately hide their names from the public on behalf of brand-name customers such as Apple. In short, the authors argue, globalization is not always helping the IT workers of the world, many of whom are working in unbearable factory conditions. From Silicon Valley to Shenzhen traces the development of the new networks of globalized mass production in the IT industry and the reorganization of work since the 1990s, capturing the systemic nature of an industry-wide restructuring of production and work in the global context. Their wide-ranging and detailed analysis makes an important contribution to ongoing academic and political debates on the globalization of production, especially by taking these debates beyond narrow perspectives of determining criteria of “success” for participation in global production networks. Rather, they emphasize the changing nature of work, employment relations, and labor policies and their implications for the possibilities of sustainable economic and social development.